Interactive Evaluator for Memory in users with Alzheimer’s Disease - Sánchez, Diego; Rincón, Raul Enrique; Olivares, Miguel Ángel; Herrera Martínez, Marcelo (TECCIENCIA, 2020)
In this document are revised different control techniques ap- plied to distributed generation systems, including control of active-reactive power, load-frequency control and the identification and control of island mode operation of the generation units, which are the main themes identified. The different control strategies identified are PID, robust, predictive and fuzzy, with applications in the aforementioned subjects. Particularly, applications for the interconnection of generation units and the control of the electric power conversion system DC-AC (inverter) are observed.